Son Preference, Sex Ratios, and Marriage Patterns - Edlund, Lena (Journal of Political Economy, 1999)
Preference for sons over daughters is widespread in many Asian countries, for example, India, China, and South Korea. This paper models endogenous sex choice and shows that unbalanced sex ratios are but one of several possible consequences of a preference for sons. In particular, if parents want children who reproduce, nonrandom mating may cause women to be consistently born into low‐status families and thus relegated to a permanent underclass. The paper also discusses possible links between son preference and marriage patterns such as spousal age gaps, hypergamy (women marrying up), caste endogamy, and cousin marriages.